Does Gender Equality Translate into Economic Equality? Evidence from about 150 Nations - Michael A. Nelson; Rajeev K. Goel (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper adds to our understanding of the causes of income inequality across nations by examining the influence of different aspects of gender equality or female empowerment. Whereas the economics of income inequality has been an area of active academic inquiry, the role of gender equality has largely been ignored. Are there positive spillovers from gender equality onto income equality? The answer to this question, using data for nearly 150 nations over the years 1985-2019, is in the affirmative. Specifically, nations with a history of women's suffrage, greater representation of women in the government, lower fertility rates, and better overall gender equality experienced lower income inequality, ceteris paribus. These results are largely supported in considerations of cross-section versus pooled data, simultaneity issues, and the measurement of income inequality. The spillovers from some dimensions of gender equality are found to be sensitive to the existing prevalence of income inequality. Policymakers ignoring the payoffs from gender empowerment on income distribution might be underinvesting in initiatives to empower women.
Keywords: D31; D63; E25; I32; J16; O15; 330; income inequality; gender inequality; suffrage; fertility; women in parliament; colonialism; GINI coefficient; government; quantile regression